ANALISIS DUGAAN PELANGGARAN PENGGUNAAN FOTOGRAFI (JEFRI TARIGAN VS TRIBUN NEWS) - Kelvin Arizona; Christine S.T. Kansil (Jurnal Hukum Adigama, 2022)
Copyright is an exclusive right owned by an author that can arise automatically based on declarative principlesafter the existence of a work which is then made into a concrete form without any reduction or restriction inaccordance with the provisions of the legislation. Copyright itself, if detailed in more detail, can be said to be aright that can be used in the context of copying a copyrighted work, which then gives the right holder anopportunity to determine restrictions on the act of duplicating his creation without permission and also the rightis limited in terms of meaning has a certain time limit on its validity. Intellectual property is attached to thecreation of the mind, and this is attached to everyone who owns the work of his creation if the work is publishedbut there will be problems if a person or legal entity uses the work of another person. There is a problem in thiswriting, namely how is the application of Law No. 28 of 2014 concerning Copyright against alleged violations ofphotographic copyright (Jefry Tarigan VS Tribun News)? This research is that not all acts of illegally takingworks are prohibited or considered copyright infringement, but in every photographic work that we call aportrait, that is, it has received protection since the portrait was uploaded. Copyright infringement can becategorized if someone does not have copyright permission from the creator and fulfills several components ofcopyright infringement, but if these components are not met, it cannot be stated that a copyright has beenviolated.